Editorial - The Australian Journal of Indigenous Education (The Australian Journal of Indigenous Education, 2015)
The challenge for any research journal today is how to continue to make the work we publish relevant, contemporary and innovative for the research groups, educational organisations, and Indigenous communities locally and globally that we serve. At the same time, we recognise it is important for us to continue our work in The Australian Journal of Indigenous Education within the critical pedagogical agenda in which it began; that is, the empowerment of Aboriginal and Torres Strait Islander peoples through education, combined with a concern to critique and challenge the national and international colonial contexts in which Indigenous education is positioned today.